Home alone [videorecording (DVD)] - Hughes, John, 1950-2009; Columbus, Chris; Culkin, Macaulay, 1980-; Pesci, Joe; Stern, Daniel, 1957-; Heard, John, 1946-2017; O'Hara, Catherine (20th Century Fox Home Entertainment, 2006)
An eight-year-old boy is left home alone on Christmas, and has to defend his home against two bumbling burglars.